Political education and legal pragmatism of Muslim organizations in India: a study of the changing nature of Muslim minority politics - Emmerich, Arndt (Asian survey, 2019)
This article discusses the involvement of Muslim organizations in disseminating political education and legal pragmatism in India. Drawing on qualitative fieldwork between 2011 and 2015, this study contributes to a better theoretical understanding of how Muslim organizations engage in democratic processes, rather than being perceived as opposed to notions of democratic participation, by examining the Popular Front of India’s promotion of rights consciousness among its followers.